Synthesis of triphenylene-based hierarchically porous monolith with nitroaromatic-sensitive fluorescence. (16th January 2023) - Satheeshkumar, Chinnadurai; Seo, Howon; Hong, Sujung; Kim, Pilhan; Seo, Myungeun
Abstract: We developed a synthetic route, based on radical polymerization, to a fluorescent monolithic hierarchically porous polymer composed of extended π-conjugated triphenylene motifs. A hexa-vinyl cross-linker containing the triphenylene core was synthesized and copolymerized with styrene in the presence of a polylactide macro-chain transfer agent to produce a cross-linked block copolymer monolith. Polymerization-induced microphase separation occurred during polymerization in situ, resulting in a disordered bicontinuous morphology of polylactide and cross-linked polystyrenic domains at a nanometer scale. Removal of polylactide generated percolating mesopores with controllable pore size and exposed micropores within the polystyrenic network. A strong bluish fluorescence was observed from the resulting porous monolith, originating from the embedded triphenylene. Fluorescence was quenched upon exposure to a solution of nitroaromatic compounds. Much stronger and faster quenching compared to the nonporous analog was attributed to the improvement in access to the triphenylene group via enhanced diffusion of the analyte through the interconnected mesopores. Graphical abstract: Image 1 Highlights: A hexavinyl conjugated cross-linker containing the triphenylene core was developed. The cross-linker was used in the polymerization-induced microphase separation process. Hierarchically porous monoliths with triphenylene groups on the micropore surface were obtained. Nitroaromatic molecules effectively quenched fluorescence from the triphenylene motif.